2007
DOI: 10.1002/anie.200605260
|View full text |Cite
|
Sign up to set email alerts
|

Triethyl Phosphite Mediated Domino Reaction: Direct Conversion of ω‐Nitroalkenes Into N‐Heterocycles

Abstract: Dominos on cycles: Several N‐heterocycles, such as 3,4‐dihydro‐2H‐1,4‐benzoxazines, 1,2,3,4‐tetrahydroquinoxalines, and 1,2,3,4‐tetrahydroquinolines, can be obtained through a novel domino reaction mediated by triethyl phosphite under the influence of microwave irradiation (MW) in a single step from nitroaromatic compounds (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…4-Methyl-2-nitrophenol (3a) [27] : Eluent: hexane-ethyl acetate (4:1) to yield a brown solid. Yield: 14%, 6.1 g. 1 H NMR (400 MHz; CDCl 3 ) 10.46 (1H, s, O H ), 7.92 (1H, m, Aryl- H ), 7.42 (1H, dd, J 8.0, 2.0, Aryl- H ), 7.08 (1H, d, J 8.8, Aryl- H ), 2.37 (3H, s, C H 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…4-Methyl-2-nitrophenol (3a) [27] : Eluent: hexane-ethyl acetate (4:1) to yield a brown solid. Yield: 14%, 6.1 g. 1 H NMR (400 MHz; CDCl 3 ) 10.46 (1H, s, O H ), 7.92 (1H, m, Aryl- H ), 7.42 (1H, dd, J 8.0, 2.0, Aryl- H ), 7.08 (1H, d, J 8.8, Aryl- H ), 2.37 (3H, s, C H 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] They are also fundamental building blocks employed in the synthesis of amines which are obtained by the reduction of the nitro group through metalacid combinations, catalytic hydrogenation, hydride transfer reductions, catalytic transfer hydrogenation and metal-free reduction methods. 10 The synthetic utility of this transformation is highlighted in several one pot procedures for the obtention of diverse structures including imines, amides 11 and a-aminophosphonates 12 together with heterocyclic compounds such as benzimidazoles, [13][14][15] quinazolinones, 16,17 pyrrolines, 18 isoindolinone derivatives, 19 tetrahydroquinolines, [20][21][22][23] and quinoxalines, 24,25 where a tandem one-pot reduction and intramolecular cyclization reaction is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…26 Krchnak et al reported tin (II)-catalyzed solid-phase cyclization of functionalized o-nitroanilines, via intramolecular nucleophilic substitution. 27 Microwave assistant reductive cyclization of substituted o-nitroaniline afforded 1,2,3,4-tetrahydroquinoxalines, as reported by Merisor et al 28 However, limitations in most cases include low yields, complicated reaction procedures and expensive catalysts. Cyclization/acylation of o-phenylenediamines with -chloroketones 29 and diboronic acid mediated cyclization/cascade transfer hydrogenation of o-phenylenediamines and o-nitroanilines with 1,2-dicarbonyl compounds, 30 are some recent examples towards more efficient synthesis of 1,2,3,4-tetrahydroquinoxalines.…”
Section: Introductionmentioning
confidence: 85%